Online decision aid for patients with prostate cancer evaluated by 11 290 patients and 91 urologists in Germany - Huber, Johannes; Karschuck, Philipp; Valdix, Johanna; Thomas, Christian; Koch, Rainer; Ihrig, Andreas; Hölscher, Tobias; Krones, Tanja; Kessler, Elke; Kliesch, Sabine; Linné, Clemens; Enders, Paul; et al. (BJU international, 2024)
Objective To evaluate the nationwide online decision aid ‘Entscheidungshilfe Prostatakrebs’ (established in 2016, >11.000 users and 60 new users/week) for patients with non-metastatic prostate cancer (PCa), from the perspective of patients and urologists. Patients and Methods To provide personalised information, the tool collects most of the International Consortium for Health Outcomes Measurement standard set, personal preferences, psychological features, and a validated rating of the tool. To evaluate urologists’ opinions, we developed a structured two-page questionnaire. All data were collected anonymously. Results From June 2016 to December 2020, 11 290 patients used the PCa decision aid. Their median (interquartile range [IQR]) age was 67 (61-72) years. The median (IQR) time from initial diagnosis to using the tool was 4 (3-7) weeks. In all, 87.7% of users reported high satisfaction. In a multivariable model, predictors for considering observation were higher knowledge, using the decision aid alone, lower oncological risk, normal erectile function, and respective personal preferences. Of 194 urologists, 91 (47%) had implemented the decision aid in their clinical practice. The urologists’ mean (SD) satisfaction score (1 ‘very good’; 6 ‘unsatisfactory’) with it was 1.45 (0.55), and 92% recommended it. Half of the urologists reported time savings. Conclusion Patients and urologists report a very high level of acceptance and satisfaction with this online tool. It offers advantages in shared decision-making and time efficiency. The usage of the decision aid might improve the adoption of active surveillance and watchful waiting when indicated.
Zuerst veröffentlicht: 20. März 2024
Gesehen am 22.08.2024